Next generation sequencing in Western Indian children with nephrolithiasis and/or nephrocalcinosis: An observational study - Anshuman Saha,; Kinnari B. Vala,; Himanshu V. Patel, (Indian Journal of Child Health, 2021)
Background: About half of children with nephrolithiasis and/or nephrocalcinosis (NL/NC) have an underlying metabolic cause. Next-generation sequencing (NGS) is increasingly being used as a clinical tool in diagnosing inherited renal diseases. Objective: The objective of the study was to retrospectively analyze the utility of NGS in the diagnosis and management of children with NL/NC at a tertiary care referral nephrology center in western India. Methods: All children ?18 years with NL/NC, where an NGS was sent from September 2016 to September 2020, were included in the study. Clinical exome sequencing covering 8882 genes was done in 13 children. The test result was interpreted as per the American College of Medical Genetics classification: No pathogenic variant, a variant of unknown significance (VUS), and likely pathogenic and pathogenic variant. Results: The median age (IQR) of the cohort at the onset of disease was 11 months (4.25–102). History of consanguinity was present in 3 children (23%). Eight children had NC 7 had NL, 7 had the end-stage renal disease (ESRD) at presentation. Seven out of 8 children with NC had ESRD. Eleven children (84.6%) had an identifiable monogenic genetic cause: 9 had pathogenic, 2 had likely pathogenic variants detected in 5 genes: AGXT, GRHPR, HOGA1, CLDN16, and HPRT1. Two VUS were detected in two children in BBS4 and KCNJ1 gene. Primary hyperoxaluria (PH) Type 1 was the most common diagnosis in 6 children. Other diagnoses were Lesch–Nyhan syndrome in 2, PH 2, PH3, and FHHNC in 1 each. Conclusion: The yield of NGS in children with NL/NC was remarkably high. NGS was useful in diagnosis and management of children with NL/NC.